STUDENTS' PERCEPTIONS OF TEACHER SELF-EFFICACY AND ITS INFLUENCE ON THEIR MOTIVATION - Brigita Woro Diyatni Kusumaningtyas; Concilianus Laos Mbato; Ouda Teda Ena (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2023)
ABSTRACTThe main purpose of this study was to examine the perception of students regarding teacher self-efficacy and its influence on their motivation in the context of learning. The researchers used mixed-method research as the research methodology. To gather the data, the researchers used some instruments, namely a questionnaire and an interview. The questionnaire was distributed to 30 undergraduate students at a university located in Yogyakarta, Indonesia. The instrument used was adopted from the Teacher's Self-Efficacy Scale Questionnaire developed by Tschannen-Moran & Hoy (2001). The data underwent both descriptive and statistical analysis using SPSS. The findings indicated that the students had a moderate degree of perceptions of teacher self-efficacy. In addition, the students' perceptions of teacher self-efficacy also influenced their motivation in learning. In other words, when students believe their lecturers have high self-efficacy in teaching, they are more motivated because they trust that the lecturers are capable of delivering the materials effectively and in an engaging manner. Therefore, it is important for lecturers to focus on building and cultivating their self-efficacy to positively influence students' learning outcomes. ABSTRAKTujuan penelitian ini adalah untuk mengetahui persepsi siswwa terhadap efikasi diri guru dan dampaknya terhadap motivasi belajar mereka. Peneliti menggunakan penelitian mixed-method sebagai metolodi penelitian. Untuk mengumpulkan data, peneliti menggunakan beberapa instrument berupa kuesioner dan interview. Peneliti menyebarkan kuesioner tersebut kepada 30 mahasiswa S1 di suatu universitas di Yogyakarta, Indonesia. Instrumen yang digunakan diadaptasi dari Kuesioner Skala Efikasi Diri Guru yang dikembangkan oleh Tschannen-Moran & Hoy (2001). Data dianalisis secara deskriptif dan statistik. Hasil penelitian menunjukan bahwa siswa mempunyai tingkat persepsi efikasi diri guru yang sedang. Selain itu, persepsi siswa terhadap efikasi diri guru juga mempengaruhi motivasi mereka dalam belajar. Dengan kata lain, ketika mahasiswa yakin bahwa dosennya memiliki efikasi diri yang tinggi dalam mengajar, maka mahasiswa akan lebih termotivasi karena yakin bahwa dosen tersebut mampu menyampaikan materi secara efektif dan menarik. Oleh karena itu, penting bagi dosen untuk fokus membangun dan menumbuhkan efikasi diri agar dapat memberikan dampak positif terhadap hasil belajar mahasiswa.How to Cite: Kusumaningtyas, B.W.D., Mbato, C.L. & Ena, O.T. (2023). Students’ Perceptions of Teacher Self-Efficacy and Its Impact on Their Motivation. IJEE (Indonesian Journal of English Education), 10(2), 428-442. doi:10.15408/ijee.v10i2.34758.